A new species of Deutonura (Collembola: Neanuridae: Neanurinae) from north-eastern Algeria, and characterisation of two intraspecific lineages by their barcodes - Deharveng, Louis; Zoughailech, Abdelmalek; Hamra-Kroua, Salah; Porco, David (Zootaxa, 2015)
A new species of Deutonura, D. zana sp. nov., is described from north-eastern Algeria. It is morphologically similar in most characters to D. deficiens meridionalis and to D. luberonensis, both members of the D. phlegraea group, differing from the former by the absence of chaeta O on head, and from the later by the separation of tubercles Di and De on Th. I. The muscular insertion pattern of the new species is figured, and suggested as a potential new character for the taxonomy of Neanurinae. Deutonura zana sp. nov. is well characterised by its barcode sequence. Within the new species as morphologically defined, two groups of COI haplotypes, in individuals indistinguishable morphologically, are reported from two distinct mountain ranges. The need of a morphological assessment of demes diverging at significant infra-specific level in their barcodes is stressed.